Analysis of Mathematical Problem-Solving Ability on Real Set - Suci Indah Sari; Zawahir Nafisah; Rohani Damayanti Sihotang; Annisaul Fadilah; Dwi Novita Sari (Riemann: Research of Mathematics and Mathematics Education, 2024)
Finding a solution to a problem is called problem-solving, therefore learning mathematics means finding solutions to problems that arise in everyday life. The purpose of this study is to characterize students' aptitude in mathematical reasoning after completing a project related to Real Analysis. This study used descriptive techniques and was quantitative. Students' logical reasoning skills were revealed from the test results they obtained while answering questions designed based on indicators of mathematical thinking skills. Data analysis techniques used in this research include surveys, data visualization, and observation. Research on students' mathematical thinking skills showed findings with high, medium, and lesser categories.